Reconstruction of Educational Science and Profession in Strengthening Teacher Professionalism Based on Islamic Values - Khatimah, Siti Husnul; Arifi, Ahmad; Wulandari, Nidya Ferry (Ahlussunnah: Journal of Islamic Education, 2025)
Teacher professionalism in the era of educational transformation and Society 5.0 faces epistemological challenges that are not only related to mastery of pedagogical and technological competencies, but also require the strengthening of moral and spiritual dimensions as the foundation of professionalism. This study aims to reconstruct Educational Science and Profession in order to strengthen teacher professionalism based on Islamic values through an integrative approach. The research used a qualitative method with a case study design conducted through field study activities, with the researcher acting as a teaching assistant in the Educational Science and Profession course at the Mathematics Education Study Program, Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Sunan Kalijaga Yogyakarta. Data collection was conducted over one semester through participatory observation of the lecture process, semi-structured interviews with lecturers and students, and analysis of learning documents, including the Semester Learning Plan, teaching modules, presentation materials, student papers, and course learning achievement instruments. The data were analyzed using thematic analysis to identify patterns of value integration, learning dynamics, and the construction of teacher professionalism. The results of the study show that the integration of Islamic values such as trustworthiness, honesty (ṣidq), intelligence (faṭānah), compassion (raḥmah), and good character (akhlak karimah) serve as an epistemological and ethical framework that enriches students' understanding of educational science and the teaching profession. This integrative approach has been proven to increase student activity, encourage critical reflection, and shape a holistic paradigm of teacher professionalism through the integration of cognitive, affective, and moral-spiritual dimensions. This research has implications for the urgency of reconstructing the education curriculum, which systematically integrates Islamic values at the epistemological, pedagogical, and axiological levels in order to build teacher professionalism that is characterful, has integrity, and is relevant to the educational needs of the present and the future.